Implementation Science: A Neglected Opportunity to Accelerate Improvements in the Safety and Quality of Surgical Care. Issue 6 (June 2017) - Hull, Louise; Athanasiou, Thanos; Russ, Stephanie
Abstract : Objective: The aim of this review was to emphasize the importance of implementation science in understanding why efforts to integrate evidence-based interventions into surgical practice frequently fail to replicate the improvements reported in early research studies. Summary of Background Data: Over the past 2 decades, numerous patient safety initiatives have been developed to improve the quality and safety of surgical care. The surgical community is now faced with translating "promising" initiatives from the research environment into clinical practice—the World Health Organization (WHO) has described this task as one of the greatest challenges facing the global health community and has identified the importance of implementation science in scaling up evidence-based interventions. Methods: Using the WHO surgical safety checklist, a prominent example of a rapidly and widely implemented surgical safety intervention of the past decade, a review of literature, spanning surgery, and implementation science, was conducted to identify and describe a broad range of factors affecting implementation success, including contextual factors, implementation strategies, and implementation outcomes. Results: Our current approach to conceptualizing and measuring the "effectiveness" of interventions has resulted in factors critical to implementing surgical safety interventions successfully being neglected. Conclusion: Improvements in the safety and quality of surgical care can be accelerated by drawing more heavily upon implementation science and that until this rapidly evolving field becomes more firmly embedded into surgical research and implementation efforts, our understanding of why interventions such as the checklist "work" in some settings and appear "not to work" in other settings will be limited. Abstract : Supplemental Digital Content is available in the text